2018
DOI: 10.1108/imefm-05-2017-0133
|View full text |Cite
|
Sign up to set email alerts
|

Empirical investigation of SMEs’ perceptions towards PLS financing in Morocco

Abstract: Purpose The main purpose of the study is to examine the willingness of Moroccan small- and medium-sized enterprises (SMEs) to adopt profit and loss sharing (PLS) method of finance and the factors that may influence their decision. Design/methodology/approach The research model is based on the decomposed theory of planned behaviour (DTPB). A total of 340 questionnaires were randomly distributed to SMEs’ owner-managers, out of which 177 were collected and only 153 were valid for analysis. Factor analysis and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 37 publications
1
26
0
2
Order By: Relevance
“…Wahyuni (2012) conducted a study in Indonesia and found that knowledge of Islamic finance principals and products is an important factor in accepting Islamic banking. In addition, Sabirzyanov (2016) highlighted the positive correlation between the level of the client's knowledge of Islamic financial contracts and their willingness to deal with Islamic banks (Badaj & Radi, 2018). Therefore, this study raises the following hypothesis:…”
Section: Self-efficacymentioning
confidence: 80%
See 4 more Smart Citations
“…Wahyuni (2012) conducted a study in Indonesia and found that knowledge of Islamic finance principals and products is an important factor in accepting Islamic banking. In addition, Sabirzyanov (2016) highlighted the positive correlation between the level of the client's knowledge of Islamic financial contracts and their willingness to deal with Islamic banks (Badaj & Radi, 2018). Therefore, this study raises the following hypothesis:…”
Section: Self-efficacymentioning
confidence: 80%
“…The search for financing is triggered by the need to cover financial requirements that may include diverging objectives as financing acquisitions, developing new products, customer segmentation or geographies, repaying loans, diversifying wealth or passing on the company (Poutziouris, 2001). In this study, suitability is measured by the extent to which Islamic modes of finance is appropriate to meet SMEs' financial requirement (Badaj & Radi, 2018). Hence, we hypothesize that attitude should be positively affected by a higher perceived adequacy of Islamic financing instruments:…”
Section: Suitabilitymentioning
confidence: 98%
See 3 more Smart Citations